Molecular characterization of wheat (Triticum species) using random amplified polymorphic DNA marker - Shende, Sarika; Walunj, Sanjay (Recent Research in Science and Technology, 2013)
Thirty five random primers were used to generate the RAPD profiles of 17 wheat accessions. Six markers that showed reproducibility were used to detect polymorphism. Based on the percentage polymorphism and unique banding profiles, five primers OPX-02, OPX-06, OPX-07, OPX-08 and OPX-09 were found to be highly discriminative. Genetic variability between wheat accessions based on Dice’s coefficient ranged from 23 to 57% across all genotypes with an average of 46%. Cluster analysis based on UPGMA method separated all the 17 wheat accessions in two distinct clusters. This low polymorphic result shows low genetic base in wheat accessions.